Byzantine Incubation Literature between Religion and Medicine: Food as Medicament in the Collection of Healing Miracles Performed by Saints Cosmas and Damian (BHG 373B) - Gollo, Giulia (Studia Ceranea, 2022)
Byzantine incubation literature is the term used in research to denote early Byzantine collections of healing miracles (5th–7th century) in which the saint’s miraculous intervention is related to the incubation experience. Despite the centrality of the concepts of disease and healing in such literature, the relationship between medicine and Christian religion needs to be further explored. Based on the Egyptian collection of Miracles of Cosmas and Damian contained in manuscript Lond. Add. 37534 (BHG 373b) as a case study, this paper intends to: (1) present those miraculous accounts where food is treated as medicament, starting from a close reading of the relevant passages; (2) looking at the (Byzantine) medical knowledge integrated in these narratives.